Mecanismos químicos e mineralógicos de transformação da magnesioferrita de solo derivado de tufito, da região do Alto Paranaíba, MG - Silva,Fernando Dias da (2009)
Magnetic soils forming on tuffite of the region of Alto Paranaíba, Minas Gerais, Brazil, usually contain iron-rich spinels exceptionally rich in magnesium and titanium. In this work, samples of the magnetically separated portion from the sand fraction of a Brunizém (Chernossolo) and from its mother-rock material were analyzed with synchrotron X-ray diffraction and 57Fe-Mössbauer spectroscopy. Magnesioferite (MgFe2O4) and maghemite (its pure non-stoichiometric spinel structure, Fe8/3 ⊕ 1/3 O4, where ⊕ = cation vacancy, corresponds to γFe2O3) were the magnetic iron oxides so identified. Basing on these data, a consistent chemical-mineralogical model is proposed for the main transformation steps involving these iron oxides in the pedosystem, starting on magnesioferrite to finally render hematite (αFe2O3), passing through maghemite as an intermediate specie.